Evaluation of pesticide combinations against brown planthopper and sheath blight in rice - ADVSLP, Anand Kumar; M, Nanda Kishore; V, Bhuvaneswari; N , Srinivasa Rao; B, Anusha (ORYZA-An International Journal of Rice, 2022)
Field experiment was conducted at Regional Agricultural Research Station, Maruteru, West Godavari (A.P.) during two kharif seasons of 2019 and 2020 to evaluate the compatibility of combinations of insecticides and fungicides against brown planthopper and sheath blight in rice. The results revealed that pymetrozine and triflumezopyrim as sole treatments are highly effective against brown planthopper (BPH), Nilaparvata lugens (Stal) by registering over 90% reduction in BPH population. While, pymetrozine and triflumezopyrim in combination with azoxystrobin and azoxystrobin + tebuconazole are highly effective against BPH and sheath blight, Rhizoctonia soloni Kuhn in by registering over 90% and >50% reduction in BPH population and sheath blight severity, respectively and registered 64.23% to 73.03% higher grain yields than untreated control. It was also found that there was no adverse effect of fungicides on the efficacy of insecticides or vice versa. The insecticides tested were physically compatible with fungicides and no phytotoxic symptoms observed on rice crop when pesticides were applied in combination. Thus, pymetrozine and triflumezopyrim are compatible with test fungicides and can be safely used as tank mix for the simultaneous management of BPH and sheath blightin rice.